Evaluasi Usability Sistem Informasi Penjualan dan Pemesanan Berbasis Web pada Coffee Peace Menggunakan Metode System Usability Scale (SUS) - Riko Riko; Kiswanto Kiswanto (Jurnal Minfo Polgan, 2026)
This study aims to evaluate the usability of a web-based sales and ordering information system at Coffee Peace using the System Usability Scale (SUS) method. The system is designed to support the ordering process and manage sales data efficiently. The research method was conducted through usability testing using a questionnaire consisting of 10 standard SUS statements distributed to 30 respondents. The evaluation focuses on measuring user perceptions in terms of effectiveness, efficiency, and satisfaction when using the system. The results show that the system is able to support the ordering process effectively and provide a positive user experience. Based on the SUS evaluation, the system obtained an average score of 94.92, which is categorized as “Excellent”. This indicates that the system has a very high level of usability and is well accepted by users. Therefore, the system can be considered effective in supporting service operations and improving user experience at Coffee Peace.